The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0003319717708070
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand Factor as a Novel Player in Valvular Heart Disease: From Bench to Valve Replacement

Abstract: von Willebrand Factor (vWF) is a well-known mediator of hemostasis and vascular inflammation. Its dynamic modulation in the bloodstream, according to hemodynamic conditions, makes it an appealing biomarker in patients with valvular heart disease (VHD). Recent studies highlight the close connection between vWF and VHD, with possible implications in the pathogenesis of VHD, promoting valve aging and calcification or favoring the development of infective endocarditis. Moreover, vWF has been recently proposed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
1
8
0
1
Order By: Relevance
“…Interestingly, our distinctly larger RETORT‐MR trial could not confirm these results. Besides the considerably different sample sizes, which could have biased the results preferentially in smaller trials, the main reason for this finding could be the time when vWFAct and vWFAg were measured: Gragnano et al analyzed vWFAct and vWFAg levels already 24 hours after percutaneous mitral valve repair, 1 whereas our study presents the levels of vWFAct and vWFAg not earlier than 4 weeks after MitraClip implantation. We deliberately chose this point of time to avoid the influence of the TMVR procedure and general anesthesia on hemostasis as it is known that stress may cause fluctuation of vWF levels 23 with unclear functional relevance.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, our distinctly larger RETORT‐MR trial could not confirm these results. Besides the considerably different sample sizes, which could have biased the results preferentially in smaller trials, the main reason for this finding could be the time when vWFAct and vWFAg were measured: Gragnano et al analyzed vWFAct and vWFAg levels already 24 hours after percutaneous mitral valve repair, 1 whereas our study presents the levels of vWFAct and vWFAg not earlier than 4 weeks after MitraClip implantation. We deliberately chose this point of time to avoid the influence of the TMVR procedure and general anesthesia on hemostasis as it is known that stress may cause fluctuation of vWF levels 23 with unclear functional relevance.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, the presence of AvWS has been described in patients with moderate to severe mitral valve dysfunction 1 . Blackshear et al investigated a population of 53 patients with mild to severe mitral regurgitation and reported that more severe mitral valve regurgitation was associated with progressive worsening of vWF activity and bleeding tendency 17 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Approximately 21% of patients with aVWS will have shear-induced activation of ADAMTS13 such as AS, hypertrophic cardiomyopathy, ventricular septal defect, left ventricular assist device, or pulmonary hypertension [ 3 ]. With regard to laboratory findings, an average of 20%-70% of moderate to severe AS patients will have increased removal of high molecular weight vWF [ 4 ]. There are a wide variety of GI pathologies that affect the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…20 Otherwise, an excessive clearance of VWF multimers by ADAMTS-13 under high shear stress (i.e., congenital heart disease, aortic stenosis, and mitral regurgitation) may result in bleeding diathesis and an acquired von Willebrand syndrome. 21 An imbalance in VWF/ADAMTS-13 axis is also involved in common thrombotic disorders, such as stroke, coronary artery disease, and venous thromboembolism (VTE). 22…”
Section: Vwf Activity Modulation: the Role Of Adamts-13mentioning
confidence: 99%